2015
DOI: 10.1007/s10653-015-9715-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cadmium and aluminum in blood samples of kidney disorder patients with drinking water and tobacco smoking: related health risk

Abstract: The combined exposure to aluminum (Al) and cadmium (Cd) causes more pronounced adverse health effects on humans. The kidneys are the main organs affected by internal exposure to Cd and Al via food and non-food items. The objective of present study was to measure the Al and Cd concentrations in cigarettes tobacco (branded and non-branded) and drinking water (domestic treated, ground and lake water) samples in southern part of Pakistan, to assess the risk due to ingestion of water and inhalation of cigarettes sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 45 publications
0
21
1
Order By: Relevance
“…However, due to limited conditions, we obtained relatively limited sample volume, which may influence partly results of probability assessment. In addition, several studies found that smoking is closely related to the Cd level [24]. However, we did not find this association, maybe due to the limited sample size and the low smoking rate.…”
Section: Discussioncontrasting
confidence: 87%
“…However, due to limited conditions, we obtained relatively limited sample volume, which may influence partly results of probability assessment. In addition, several studies found that smoking is closely related to the Cd level [24]. However, we did not find this association, maybe due to the limited sample size and the low smoking rate.…”
Section: Discussioncontrasting
confidence: 87%
“…Owing to rapid industrial development, the increase in the human population and the use of increasingly greater amounts of chemical products, pollution of water, soil, and air poses a great threat [ 1 ]. Heavy metals are a particularly dangerous type of pollution as they do not undergo biodegradation and can accumulate in the human body and ecosystems [ 2 ]. The most common heavy metals include lead, arsenic, mercury, copper, and cadmium [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other strong metal relationship found at both sites is between Cd and Al. These two metals are found related in cigarette smoke and therefore this could be a variable associated with these two metals [25]. However, the levels of Al and Cd in Vieques samples are much higher than those from the Main Island and are associated with females and in the age group of 34-54 years, suggesting that there is an additional variable involved with the Vieques residents.…”
Section: Discussionmentioning
confidence: 91%